Family planning as an investment in development: Evaluation of a program's consequences in Matlab, Bangladesh - Shareen Joshi; T. Paul Schultz (Yale University, Economic Growth Center, 2007)
The paper analyzes 141 villages in Matlab, Bangladesh from 1974 to 1996, in which half the villages received from 1977 to 1996 a door-to-door outreach family planning and maternalchild health program. Village and individual data confirm a decline in fertility of about 15 percent in the program villages compared with the control villages by 1982 , as others have noted, which persists until 1996. The consequences of the program on a series of long run family welfare outcomes are then estimated in addition to fertility : women's health, earnings and household assets, use of preventive health inputs, and finally the inter-generational effects on the health and schooling of the woman's children. Within two decades many of these indicators of the welfare of women and their children improve significantly in conjunction with the programinduced decline in fertility and child mortality. This suggests social returns to this reproductive health program in rural South Asia have many facets beyond fertility reduction, which do not appear to dissipate over two decades.
Keywords: O12; J13; I12; J16; 330; Fertility; family planning; gender and development; program evaluation; Bangladesh